IMMORTALITY YET? Or, the permanence of Mary Douglas. Issue 4 (1st August 2018) - Fardon, Richard
Abstract : There is no absolute measure for the lasting impact of work by anthropologists. However, the scholarship of Mary Douglas has achieved wide‐ranging interdisciplinary recognition. Here the author considers ways in which her work has impacted scholarship.